Effect of cadmium chloride on the haematological profiles of the freshwater ornamental fish, Cyprinus carpio koi (Linnaeus, 1758) - Ali, A. Jawahar; Akbar, N. Jalaluddin; Kumar, M. S. Arun; John, Akbar (Zibeline International Publishing, 2018)
Haematological profile [Haemoglobin (Hb), White Blood Corpuscles (WBC), Red Blood Corpuscles (RBC), Packed Cell Volume (PCV), Mean Corpuscular Volume (MCV), Mean Corpuscular Haemoglobin (MCH), Mean Corpuscular Haemoglobin concentration (MCHC) and Platelets count (PLT)] of the freshwater ornamental fish, Cyprinus carpio koi exposed to 1/10th of 96hrs LC50 (92.5 ppm) sublethal concentration of Cadmium chloride for a period of 30 days were checked. Compared to control, significant decrease in Hb, RBC, PCV, MCH, MCHC and PLT were noted (P < 0.05) while WBC and MCV values were significantly increased (P < 0.05). Observation of haematological parameters allows the most rapid detection of alterations in fish after the exposure with xenobiotic compounds and thus, it could be concluded that the haematological indices could be considered as possible biomarkers for heavy metal pollution.